DEVELOPMENT OF DISTRIBUTED FIBRE OPTIC INCLINOMETER FOR GROUND MOVEMENT DETECTION - GHAZALI, MUHAMMAD FARID (2020)
Subsurface ground deformation monitoring is an important aspect for controlling subsurface ground movement in particularly deep excavations and forewarning of geological disasters such as landslides, land subsidence, ground fissure, and surface collapse. Inclinometer and extensometer are examples of the conventional geotechnical instruments to monitor such ground movement. However, most conventional geotechnical instruments have certain limitations including discrete sensing (they may miss the exact location of soil movement), high cost, and susceptible to various reading errors. Recently the advancement of Distributed Optical Fibre Strain Sensing (DOFSS) has been introduced in geo-structure monitoring purpose.